Age at migration and social integration - Olof Aslund; Anders Bohlmark; Oskar Nordstrom Skans (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
The paper studies childhood migrants and examines how age at migration affects their ensuing integration at the residential market, the labor market, and the marriage market. We use population-wide Swedish data and compare outcomes as adults among siblings arriving at different ages in order to ensure that the results can be given a causal interpretation. The results show that the children who arrived at a higher age had substantially lower shares of natives among their neighbors, coworkers and spouses as adults. The effects are mostly driven by higher exposure to immigrants of similar ethnic origin, in particular at the marriage market. There are also non-trivial effects on employment, but a more limited impact on education and wages. We also analyze children of migrants and show that parents' time in the host country before child birth matters, which implies that the outcomes of the social integration process are inherited. Inherited integration has a particularly strong impact on the marriage patterns of females.
Keywords: J12; J15; J13; J01; 330; Immigration; integration; segregation; age at migration; siblings